2012
DOI: 10.1158/1535-7163.mct-11-0989
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of BRAF, MEK, and PI3K/mTOR Inhibitors Overcome Acquired Resistance to the BRAF Inhibitor GSK2118436 Dabrafenib, Mediated byNRASorMEKMutations

Abstract: Recent results from clinical trials with the BRAF inhibitors GSK2118436 (dabrafenib) and PLX4032 (vemurafenib) have shown encouraging response rates; however, the duration of response has been limited. To identify determinants of acquired resistance to GSK2118436 and strategies to overcome the resistance, we isolated GSK2118436 drug-resistant clones from the A375 BRAF V600E and the YUSIT1 BRAF V600K melanoma cell lines. These clones also showed reduced sensitivity to the allosteric mitogen-activated protein/ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
269
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(278 citation statements)
references
References 41 publications
9
269
0
Order By: Relevance
“…It has recently been demonstrated that cotargeting of the MEK/ERK and PI3K/mTOR pathways with MEKi+AKTi and MEKi+mTORi 1 is effective in BRAF mutant cells with acquired resistance to BRAF inhibitors due to activating mutations in NRAS (26,27). Although these combinations also decreased cell growth in our panel of 10 human NRAS mutant melanoma cell lines, we observed that it was less effective in decreasing cell viability than MEKi+PI3K/mTORi 1,2 .…”
Section: Discussionmentioning
confidence: 58%
“…It has recently been demonstrated that cotargeting of the MEK/ERK and PI3K/mTOR pathways with MEKi+AKTi and MEKi+mTORi 1 is effective in BRAF mutant cells with acquired resistance to BRAF inhibitors due to activating mutations in NRAS (26,27). Although these combinations also decreased cell growth in our panel of 10 human NRAS mutant melanoma cell lines, we observed that it was less effective in decreasing cell viability than MEKi+PI3K/mTORi 1,2 .…”
Section: Discussionmentioning
confidence: 58%
“…MEK1/2 inhibitors used with EGFR or VEGFR TKIs have demonstrated growth inhibition, antiangiogenesis, and curbed metastasis. Resistance to a BRAF inhibitor (BRAFi) dabrafenib, attributed to mutations in NRAS or MEK, was restored when melanoma cells were co-treated with dabrafenib and a MEK inhibitor (MEKi) trametinib [92,93]. This combination treatment was subsequently approved by the FDA in 2014 for therapy for advanced melanoma.…”
Section: Simultaneously Targeting Major Oncogenic Pathways By Multiplmentioning
confidence: 99%
“…Another approach is to target multiple signaling pathways simultaneously, and thus prevent the cancer cell from changing its dependency to another signaling pathway. There is considerable preclinical evidence supporting this approach, for example, in the setting of combining inhibitors of mitogen-activated protein (MAP)-extracellular signal-regulated kinase (ERK) kinase (MEK; MAP kinase kinase, MAP2K) with inhibitors of PI3 kinase (phosphatidylinositol 3-kinase, PIK3CA) or (2-7) BRAF (8)(9)(10), and these combinations are beginning to show efficacy in the clinic (11). A third approach to enhancing the efficacy of targeted therapy is to simultaneously target downstream proteins that protect tumor cells from apoptosis and thus increase overall cell killing (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%